The Role Of Spiritual And Ideological Education In Shaping The Socio-Spiritual Image Of Unorganized Youth - Zumrad Kasimova (Zien Journals, 2022)
This article discusses the content of youth policy implemented in Uzbekistan during the years of independence, some issues related to the ideological upbringing of young people not covered by education
Keywords: Youth; education; upbringing; spirituality